The Perspective of Young Adults Who Experience Homelessness About the Links Between Music and the Psychoactive Substance Use Trajectory - Cournoyer Lemaire, Élise (Journal of drug issues, 2024)
This study aimed to describe and understand the links between musical activities (i.e. listening, playing, attending festive events, belonging to music-based communities) and the addictive trajectory of homeless young adults who experience problematic psychoactive substance (PS) use. Semi-structured qualitative interviews were conducted with 15 homeless young adults aged 18 to 30 years old, to explore how music modulated their addictive trajectory. A thematic and trajectory analysis were performed. Music most often constituted a tool used to control, reduce, or recover from problematic PS use, and sometimes led to the initiation of novel substances, increased consumption, and relapses. These benefits and harms varied according to specific individual and contextual factors. Almost half of the sample reported no link between music and PS use. A better comprehension of the links between music and the addictive trajectory will guide the development of adapted harm reduction interventions that account for homeless young adults’ strengths.